Tree-kangaroos of Australia and New Guinea - Martin, Roger (Roger William), 1946- (Australian natural history series., 2005)
To many people, the suggestion that a kangaroo could live up a tree is fantasy. Yet, in the rainforests of Far North Queensland and New Guinea, there are extraordinary kangaroos that do just that. Many aspects of these marsupials' anatomy and biology suggest a terrestrial kangaroo ancestor. Yet no one has, so far, come forward with a convincing explanation of how, why and when mammals that was so superbly adapted for life on the ground should end up back in the trees.